Adaptive platform trials: the impact of common controls on type one error and power - Nguyen, Quynh; Hees, Katharina; Hofner, Benjamin (Journal of Biopharmaceutical Statistics, 2023)
Platform trials offer a framework to study multiple interventions in one trial with the opportunity of opening and closing arms. The use of common controls can increase efficiency as compared to individual controls. The need for multiplicity adjustment because of common controls is currently a debate among researchers, pharmaceutical companies, and regulators. The impact of common controls on the type one error in a fixed platform trial, i.e. when all treatments start and end recruitment at the same time, has been discussed in the literature before. We complement these findings by investigating the impact of a common control on the type one error and power in a flexible platform trial, i.e. when one arm joins the platform later. We derived the correlation of test statistics to assess the impact of the overlap and compared the results to a trial with individual controls. Furthermore, we evaluate the power, and the impact of multiplicity adjustment on the power in fixed and flexible platform trials. These methodological considerations are complemented by a regulatory guideline review. With multiple arms, the FWER is inflated when no multiplicity adjustment is applied. However, the FWER inflation is smaller with common controls than with individual controls. Even after multiplicity adjustment, a trial with common controls is often beneficial in terms of sample size and power. However, in some cases, the trial with common controls loses the efficiency gain and it might be advisable to run a separate trial rather than joining a platform trial.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Common control; platform trial; power; type I error

Amino Alcohol- (NPS-2143) and Quinazolinone-Derived Calcilytics (ATF936 and AXT914) Differentially Mitigate Excessive Signalling of Calcium-Sensing Receptor Mutants Causing Bartter Syndrome Type 5 and Autosomal Dominant Hypocalcemia - Letz, Saskia; Haag, Christine; Schulze, Egbert; Frank-Raue, Karin; Raue, Friedhelm; Hofner, Benjamin; Mayr, Bernhard; Schöfl, Christof (PLoS ONE, 2014)
Activating calcium sensing receptor (CaSR) mutations cause autosomal dominant hypocalcemia (ADH) characterized by low serum calcium, inappropriately low PTH and relative hypercalciuria. Four activating CaSR mutations cause additional renal wasting of sodium, chloride and other salts, a condition called Bartter syndrome (BS) type 5. Until today there is no specific medical treatment for BS type 5 and ADH. We investigated the effects of different allosteric CaSR antagonists (calcilytics) on activating CaSR mutants.All 4 known mutations causing BS type 5 and five ADH mutations were expressed in HEK 293T cells and receptor signalling was studied by measurement of intracellular free calcium in response to extracellular calcium ([Ca2+]o). To investigate the effect of calcilytics, cells were stimulated with 3 mM [Ca2+]o in the presence or absence of NPS-2143, ATF936 or AXT914.All BS type 5 and ADH mutants showed enhanced signalling activity to [Ca2+]o with left shifted dose response curves. In contrast to the amino alcohol NPS-2143, which was only partially effective, the quinazolinone calcilytics ATF936 and AXT914 significantly mitigated excessive cytosolic calcium signalling of all BS type 5 and ADH mutants studied. When these mutants were co-expressed with wild-type CaSR to approximate heterozygosity in patients, ATF936 and AXT914 were also effective on all mutants.The calcilytics ATF936 and AXT914 are capable of attenuating enhanced cytosolic calcium signalling activity of CaSR mutations causing BS type 5 and ADH. Quinazolinone calcilytics might therefore offer a novel treatment option for patients with activating CaSR mutations.
EVALuna2:1857

An Update on Statistical Boosting in Biomedicine - Mayr, Andreas; Hofner, Benjamin; Waldmann, Elisabeth; Hepp, Tobias; Meyer, Sebastian; Gefeller, Olaf (Computational and Mathematical Methods in Medicine, 2017)
Statistical boosting algorithms have triggered a lot of research during the last decade. They combine a powerful machine learning approach with classical statistical modelling, offering various practical advantages like automated variable selection and implicit regularization of effect estimates. They are extremely flexible, as the underlying base-learners (regression functions defining the type of effect for the explanatory variables) can be combined with any kind of loss function (target function to be optimized, defining the type of regression setting). In this review article, we highlight the most recent methodological developments on statistical boosting regarding variable selection, functional regression, and advanced time-to-event modelling. Additionally, we provide a short overview on relevant applications of statistical boosting in biomedicine.
EVALuna2:34211

Appetite regulating Hormone and its Relationship to the Functionality in older Adults - Diekmann, R.; Hofner, Benjamin; Uter, Wolfgang; Schusdziarra, V.; Kaiser, M.; Vidal, K.; Sieber, Cornel; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Boosting for statistical modelling: A non-technical introduction - Mayr, Andreas; Hofner, Benjamin (Statistical Modelling, 2018)
Boosting algorithms were originally developed for machine learning but were later adapted to estimate statistical models-offering various practical advantages such as automated variable selection and implicit regularization of effect estimates. The interpretation of the resulting models, however, remains the same as if they had been fitted by classical methods. Boosting, hence, allows to use an advanced machine learning scheme to estimate various types of statistical models. This tutorial aims to highlight how boosting can be used for semi-parametric modelling, what practical implications follow from the design of the algorithm and what kind of drawbacks data analysts have to expect. We illustrate the application of boosting in the analysis of a stunting score from children in India and a high-dimensional dataset of tumour DNA to develop a biomarker for the occurrence of metastases in breast cancer patients.
EVALuna2:35670

Boosting the discriminatory power of sparse survival models via optimization of the concordance index and stability selection - Mayr, Andreas; Hofner, Benjamin; Schmid, Matthias (BMC Bioinformatics, 2016)
When constructing new biomarker or gene signature scores for time-to-event outcomes, the underlying aims are to develop a discrimination model that helps to predict whether patients have a poor or good prognosis and to identify the most influential variables for this task. In practice, this is often done fitting Cox models. Those are, however, not necessarily optimal with respect to the resulting discriminatory power and are based on restrictive assumptions. We present a combined approach to automatically select and fit sparse discrimination models for potentially high-dimensional survival data based on boosting a smooth version of the concordance index (C-index). Due to this objective function, the resulting prediction models are optimal with respect to their ability to discriminate between patients with longer and shorter survival times. The gradient boosting algorithm is combined with the stability selection approach to enhance and control its variable selection properties.The resulting algorithm fits prediction models based on the rankings of the survival times and automatically selects only the most stable predictors. The performance of the approach, which works best for small numbers of informative predictors, is demonstrated in a large scale simulation study: C-index boosting in combination with stability selection is able to identify a small subset of informative predictors from a much larger set of non-informative ones while controlling the per-family error rate. In an application to discover biomarkers for breast cancer patients based on gene expression data, stability selection yielded sparser models and the resulting discriminatory power was higher than with lasso penalized Cox regression models.The combination of stability selection and C-index boosting can be used to select small numbers of informative biomarkers and to derive new prediction rules that are optimal with respect to their discriminatory power. Stability selection controls the per-family error rate which makes the new approach also appealing from an inferential point of view, as it provides an alternative to classical hypothesis tests for single predictor effects. Due to the shrinkage and variable selection properties of statistical boosting algorithms, the latter tests are typically unfeasible for prediction models fitted by boosting.
EVALuna2:5549

Bouldering psychotherapy reduces depressive symptoms even when general physical activity is controlled for: A randomized controlled trial - Stelzer, Eva-Maria; Book, Stephanie; Grässel, Elmar; Hofner, Benjamin; Kornhuber, Johannes; Luttenberger, Katharina (Heliyon, 2018)
Background: Bouldering psychotherapy (BPT) combines psychotherapeutic elements with physical activity (PA). It might be effective for reducing symptoms of depression, but so far, no study has assessed individuals' levels of PA to control for whether positive effects on depression can also be found when adjusting for participants' levels of PA. This is important because PA itself has been proven effective in reducing depression and therefore might be an important variable to account for - especially in therapies using sport as one therapeutic mechanism. Methods: Using a waitlist control group design, outpatients with depression were assessed at baseline and after eight, 16, and 24 weeks. The intervention group took part in an eight-week bouldering psychotherapy which met once a week for three hours. Self-report measures before and after the intervention included the Symptom Checklist-90-R (SCL-90-R), the Beck Depression Inventory (BDI-II), and the questionnaire on resources and self-management skills (FERUS). PA was assessed during the first 16-week period via FitBit Zip accelerometers. Results: Altogether, 47 complete cases (20 men and 27 women) were included in the final analyses. Depression scores dropped by up to 6.74 (CI 2.80-10.67) points on the SCL-90-R depression scale and by up to 8.26 (CI 4.21-12.31) points on the BDI-II during the BPT intervention, the control group remained stable (SCL-90-R Cohen's d = 0.60; BDI-II: Cohen's d = .50). All Participants accrued an average of 6,515 steps per day, which is considered "low-active." Participants of the BPT intervention were significantly more likely to reduce their depressive symptoms (p = .025) than participants of the control group, even when PA was controlled for in a regression analysis. Limitations: Limitations of the study are the relatively small number of patients and the assessment of outcome scores via self-report. Conclusions: This study provides evidence that short-term BPT can be effective for reducing symptoms of depression even if controlled for other therapeutically active confounders including antidepressant medication, psychotherapy and general level of PA.
EVALuna2:211633

Controlling false discoveries in high-dimensional situations: boosting with stability selection - Hofner, Benjamin; Boccuto, Luigi; Goeker, Markus (BMC Bioinformatics, 2015)
Modern biotechnologies often result in high-dimensional data sets with many more variables than observations (n<<p). These data sets pose new challenges to statistical analysis: Variable selection becomes one of the most important tasks in this setting. Similar challenges arise if in modern data sets from observational studies, e.g., in ecology, where flexible, non-linear models are fitted to high-dimensional data. We assess the recently proposed flexible framework for variable selection called stability selection. By the use of resampling procedures, stability selection adds a finite sample error control to high-dimensional variable selection procedures such as Lasso or boosting. We consider the combination of boosting and stability selection and present results from a detailed simulation study that provide insights into the usefulness of this combination. The interpretation of the used error bounds is elaborated and insights for practical data analysis are given.Stability selection with boosting was able to detect influential predictors in high-dimensional settings while controlling the given error bound in various simulation scenarios. The dependence on various parameters such as the sample size, the number of truly influential variables or tuning parameters of the algorithm was investigated. The results were applied to investigate phenotype measurements in patients with autism spectrum disorders using a log-linear interaction model which was fitted by boosting. Stability selection identified five differentially expressed amino acid pathways.Stability selection is implemented in the freely available R package stabs (http://CRAN.R-project.org/package=stabs). It proved to work well in high-dimensional settings with more predictors than observations for both, linear and additive models. The original version of stability selection, which controls the per-family error rate, is quite conservative, though, this is much less the case for its improvement, complementary pairs stability selection. Nevertheless, care should be taken to appropriately specify the error bound.
EVALuna2:5507

Diagnostic and prognostic performance of multiple biomarkers for acute heart failure in older patients presenting to the emergency department - Bahrmann, A.; Hofner, Benjamin; Bertsch, T.; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, Philipp (European Heart Journal, 2014)

"EduKation demenz®". Psychoeducative training program for relatives of people with dementia - Engel, Sabine; Reiter-Jaeschke, A.; Hofner, Benjamin (Zeitschrift für Gerontologie und Geriatrie, 2016)
During the course of dementia there is frequently a decline in the quality of interpersonal relationships between the patient and the family caregivers. This is mainly caused by a very critical attitude of the family caregiver to the patient and by the limited ability of the family caregiver to empathically communicate with the patient. This relational disorder significantly contributes to the perceived burden of the family caregiver.This study was carried out to investigate whether the ability of family caregivers to empathically communicate can be strengthened, their emotional attitude towards the patient can be improved and their perceived burden and symptoms of depression can be reduced through a special communication-oriented psychoeducational intervention.Within the framework of a controlled study for confounding factors 121 family caregivers participated in a 10-week group intervention "EduKation demenz®," whereas the 93 family caregivers of the control group received detailed self-help literature. The before and after surveys were conducted using a standardized questionnaire.Compared to the control group the intervention group displayed a statistically significant difference in all target parameters: more empathic communication with the patient (confounder-controlled difference of change in the intervention group versus control group 0.69, p = 0.023), a less critical attitude towards the patient (confounder-controlled difference of change in the intervention group versus control group 2.11, p = 0.027), reduction in the perceived burden from disrupted communication (confounder-controlled difference of change in the intervention group versus control group 1.76, p = 0.038) and decreased symptoms of depression for caregivers with >= 33 points in the general depression scale (ADS-K, p = 0.028).Family caregivers of people with dementia clearly did not benefit from direct information transfer through the extensive offer of self-help literature to the same extent as the psychoeducational group intervention.
EVALuna2:5557

Fracture Rates and Lifetime Estimations of CAD/CAM All-ceramic Restorations - Belli, Renan; Petschelt, Anselm; Hofner, Benjamin; Hajto, J.; Scherrer, S. S.; Lohbauer, Ulrich (Journal of Dental Research, 2016)
The gathering of clinical data on fractures of dental restorations through prospective clinical trials is a labor- and time-consuming enterprise. Here, we propose an unconventional approach for collecting large datasets, from which clinical information on indirect restorations can be retrospectively analyzed. The authors accessed the database of an industry-scale machining center in Germany and obtained information on 34,911 computer-aided design (CAD)/computer-aided manufacturing (CAM) all-ceramic posterior restorations. The fractures of bridges, crowns, onlays, and inlays fabricated from different all-ceramic systems over a period of 3.5 y were reported by dentists and entered in the database. Survival analyses and estimations of future life revealed differences in performance among ZrO2-based restorations and lithium disilicate and leucite-reinforced glass-ceramics.
EVALuna2:5537

Geodermatophilus poikilotrophi sp. nov.: a multitolerant actinomycete isolated from dolomitic marble - Del Carmen Montero-Calasanz, Maria; Hofner, Benjamin; Goeker, Markus; Rohde, Manfred; Sproeer, Cathrin; Hezbri, Karima; Gtari, Maher; Schumann, Peter; Klenk, Hans-Peter (BioMed Research International, 2014)
A novel Gram-reaction-positive, aerobic actinobacterium, tolerant to mitomycin C, heavy metals, metalloids, hydrogen peroxide, desiccation, and ionizing- and UV-radiation, designated G18T, was isolated from dolomitic marble collected from outcrops in Samara (Namibia). The growth range was 15-35°C, at pH 5.5-9.5 and in presence of 1% NaCl, forming greenish-black coloured colonies on GYM Streptomyces agar. Chemotaxonomic and molecular characteristics of the isolate matched those described for other representatives of the genus Geodermatophilus. The peptidoglycan contained meso-diaminopimelic acid as diagnostic diaminoacid. The main phospholipids were phosphatidylethanolamine, phosphatidylcholine, phosphatidylinositol, and small amount of diphosphatidylglycerol. MK-9(H4) was the dominant menaquinone and galactose was detected as diagnostic sugar. The major cellular fatty acids were branched-chain saturated acids iso-C16:0 and iso-C15:0 and the unsaturated C17:1 ?8c and C16:1 ?7c. The 16S rRNA gene showed 97.4-99.1% sequence identity with the other representatives of genus Geodermatophilus. Based on phenotypic results and 16S rRNA gene sequence analysis, strain G18T is proposed to represent a novel species, Geodermatophilus poikilotrophi. Type strain is G18T (=DSM 44209T=CCUG 63018T). The INSDC accession number is HF970583. The novel R software package lethal was used to compute the lethal doses with confidence intervals resulting from tolerance experiments.
EVALuna2:5475

Gradient boosting for distributional regression: faster tuning and improved variable selection via noncyclical updates - Thomas, Janek; Mayr, Andreas; Bischl, Bernd; Schmid, Matthias; Smith, Adam; Hofner, Benjamin (Statistics and Computing, 2018)
We present a new algorithm for boosting generalized additive models for location, scale and shape (GAMLSS) that allows to incorporate stability selection, an increasingly popular way to obtain stable sets of covariates while controlling the per-family error rate. The model is fitted repeatedly to subsampled data, and variables with high selection frequencies are extracted. To apply stability selection to boosted GAMLSS, we develop a new "noncyclical" fitting algorithm that incorporates an additional selection step of the best-fitting distribution parameter in each iteration. This new algorithm has the additional advantage that optimizing the tuning parameters of boosting is reduced from a multi-dimensional to a one-dimensional problem with vastly decreased complexity. The performance of the novel algorithm is evaluated in an extensive simulation study. We apply this new algorithm to a study to estimate abundance of common eider in Massachusetts, USA, featuring excess zeros, overdispersion, nonlinearity and spatiotemporal structures. Eider abundance is estimated via boosted GAMLSS, allowing both mean and overdispersion to be regressed on covariates. Stability selection is used to obtain a sparse set of stable predictors.
EVALuna2:35678

Linear or smooth? Enhanced model choice in boosting via deselection of base-learners - Mayr, Andreas; Wistuba, Tobias; Speller, Jan; Gude, Francisco; Hofner, Benjamin (Statistical Modelling, 2023)
The specification of a particular type of effect (e.g., linear or non-linear) of a covariate in a regression model can be either based on graphical assessment, subject matter knowledge or also on data-driven model choice procedures. For the latter variant, we present a boosting approach that is available for a huge number of different model classes. Boosting is an indirect regularization technique that leads to variable selection and can easily incorporate also non-linear or smooth effects. Furthermore, the algorithm can be adapted in a way to automatically select whether to model a continuous variable with a smooth or a linear effect. We enhance this model choice procedure by trying to compensate the inherent bias towards the more complex effect by incorporating a pragmatic and simple deselection technique that was originally implemented for enhanced variable selection. We illustrate our approach in the analysis of T3 thyroid hormone levels from a larger Galician cohort and investigate its performance in a simulation study.
CRIS-Team Scopus Importer:2023-09-01
Keywords: boosting; model choice; prediction modelling; sparsity; splines

Long-term Results of Conservative Therapy of Adolescent Idiopathic Scoliosis Using the Cheneau Brace - Weniger, Carmen Dorothea; Fujak, Albert; Hofner, Benjamin; Fuchs, Markus; Forst, Raimund; Richter, Richard Heinrich (Klinische Pädiatrie, 2019)
Adolescent idiopathic scoliosis is a disease of the growing skeleton. The goal in therapy is to decelerate or to prevent progression of the spinal curve. As part of a retrospective study the patient group of the scoliosis surgery from 1995-2016 was analysed according to the inclusion criteria of the Scoliosis research Society (SRS). 159 of 643 of the patients fullfilled the specific criteria. The assessment of effectiveness was based on the progression of the angle of curvature. If it was ≤5° it was judged positively. The therapy in accordance to Cheneau is a full-time bracing orthosis. Data from 159 patients - 136 fem. (85.5%), 23 male (14.5%) was analysed. The average age at the beginning of treatment was 13.3±1.7 years. The average duration was 3.47±1.2 years. The average Cobb-angle before treatment was 28.39°±9.44°. At the completion is was 27.7°±12.34°. Stabilisation of scoliosis (≤5°) was achieved for 136 of the patients (85.5%). The final follow-up showed a progression of the Cobb angel>5° in 23 cases, of which 19 had to undergo secondary surgery. The length of therapy had a positive influence (p=0.057) on the result. Brace treatment constitutes an effective method of therapy at curvatures between 20-40°. Short duration of therapy correlates with a expressively increased risk towards progression (p=0.057). The Cheneau brace treatment constitutes an effective treatment at curvature angles between 20-40°. The risk of progression can be reduced by a timely and correct identification.
CRIS-Team Scopus Importer:2019-09-17

Marketing authorisation for rare diseases: The European regulatory perspective using the example of gene and cell therapies Arzneimittelzulassung im Bereich seltener Erkrankungen: die europäische regulatorische Perspektive am Beispiel der Gen- und Zelltherapeutika - Schüßler-Lenz, Martina; Hofner, Benjamin (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2024)
Technological and scientific innovations in the area of gene and cell therapies, so-called advanced therapy medicinal products (ATMPs), have contributed to the steep increase in treatment options for patients with rare diseases. They offer opportunities to address the underlying genetic defect by gene addition, i.e., the delivery of the gene of interest to the target cells, or by genome editing approaches through direct repair of disease-causing mutations. This paper outlines clinical evidence requirements in the context of marketing authorisations for rare diseases. Two out of fifteen gene therapies that have been approved in the European Union since 2018 are used as case studies: Libmeldy (atidarsagen autotemcel) for the treatment of patients with metachromatic leukodystrophy, and Roctavian (valoctocogen roxaparvovec) for the treatment of patients with haemophilia A. Special aspects of the evaluation of single-arm trials with small sample size and requirements with regard to the isolation and causal attribution of the treatment effect are discussed. The role of clinical data obtained under everyday conditions (real world data) to support the generation of evidence in the pre- and post authorisation phase is critically examined. Furthermore, the paper outlines aspects related to conditional versus standard marketing authorisations as well as aspects related to registry-based non-interventional studies in the context of market and patient access to urgently needed drugs.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Clinical evidence; Gene and cell therapies; Marketing authorization; Rare diseases

Modeling spatiotemporal abundance of mobile wildlife in highly variable environments using boosted GAMLSS hurdle models - Smith, Adam; Hofner, Benjamin; Lamb, Juliet S.; Osenkowski, Jason; Allison, Taber; Sadoti, Giancarlo; Mcwilliams, Scott R.; Paton, Peter (Ecology and Evolution, 2019)
Modeling organism distributions from survey data involves numerous statistical challenges, including accounting for zero-inflation, overdispersion, and selection and incorporation of environmental covariates. In environments with high spatial and temporal variability, addressing these challenges often requires numerous assumptions regarding organism distributions and their relationships to biophysical features. These assumptions may limit the resolution or accuracy of predictions resulting from survey-based distribution models. We propose an iterative modeling approach that incorporates a negative binomial hurdle, followed by modeling of the relationship of organism distribution and abundance to environmental covariates using generalized additive models (GAM) and generalized additive models for location, scale, and shape (GAMLSS). Our approach accounts for key features of survey data by separating binary (presence-absence) from count (abundance) data, separately modeling the mean and dispersion of count data, and incorporating selection of appropriate covariates and response functions from a suite of potential covariates while avoiding overfitting. We apply our modeling approach to surveys of sea duck abundance and distribution in Nantucket Sound (Massachusetts, USA), which has been proposed as a location for offshore wind energy development. Our model results highlight the importance of spatiotemporal variation in this system, as well as identifying key habitat features including distance to shore, sediment grain size, and seafloor topographic variation. Our work provides a powerful, flexible, and highly repeatable modeling framework with minimal assumptions that can be broadly applied to the modeling of survey data with high spatiotemporal variability. Applying GAMLSS models to the count portion of survey data allows us to incorporate potential overdispersion, which can dramatically affect model results in highly dynamic systems. Our approach is particularly relevant to systems in which little a priori knowledge is available regarding relationships between organism distributions and biophysical features, since it incorporates simultaneous selection of covariates and their functional relationships with organism responses.
CRIS-Team WoS Importer:2019-03-22

Multiple biomarkers for risk stratification of unselected older patients in the emergency department - Bahrmann, Philipp; Bahrmann, A.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bertsch, T. (European Heart Journal, 2015)

Multiple biomarker strategy for improved diagnosis of acute heart failure in older patients presenting to the emergency department - Bahrmann, Philipp; Bahrmann, Anke; Hofner, Benjamin; Christ, Michael; Achenbach, Stephan; Sieber, Cornel; Bertsch, Thomas (European Heart Journal: Acute Cardiovascular Care, 2015)
Biomarkers can help to identity acute heart failure (AHF) as the cause of symptoms in patients presenting to the emergency department (ED). Older patients may prove a diagnostic challenge due to co-morbidities. Therefore we prospectively investigated the diagnostic performance of N-terminal pro-B-type natriuretic peptide (NT-proBNP) alone or in combination with other biomarkers for AHF upon admission at the ED.302 non-surgical patients aged >= 70 years were consecutively enrolled upon admission to the ED. In addition to NT-proBNP, mid-regional pro-adrenomedullin (MR-proADM), mid-regional pro-atrial natriuretic peptide (MR-proANP), C-terminal pro-endothelin-1 (CT-proET-1) and ultra-sensitive C-terminal pro-vasopressin (Copeptin-us) were measured at admission. Two cardiologists independently adjudicated the final diagnosis of AHF after reviewing all available baseline data excluding the biomarkers. We assessed changes in C-index, integrated discrimination improvement (IDI), and net reclassification improvement (NRI) for the multimarker approach.AHF was diagnosed in 120 (40%) patients (age 81±6 years, 64 men, 56 women). Adding MR-ADM to NT-proBNP levels improved C-index (0.84 versus 0.81; p=0.045), and yielded IDI (3.3%; p=0.002), NRI (17%, p<0.001) and continuous NRI (33.3%; p=0.002). Adding CT-proET-1 to NT-proBNP levels improved C index (0.86 versus 0.81, p=0.031), and yielded robust IDI (12.4%; p<0.001), NRI (31.3%, p<0.001) and continuous NRI (69.9%; p<0.001). No other dual or triple biomarker combination showed a significant improvement of both C-index and IDI.In older patients presenting to the ED, the addition of CT-proET-1 or MR-proADM to NT-proBNP improves diagnostic accuracy of AHF. Both dual biomarker approaches offer significant risk reclassification improvement over NT-proBNP.
EVALuna2:5476

Musculoskeletal symptoms in patients with post-polio syndrome - Balzien, B.; Hofner, Benjamin; Harlander-Weikert, E.; Frommelt, P.; Bork, H.; Forst, Raimund; Fujak, A. (Zeitschrift für Orthopädie und Unfallchirurgie, 2014)
The prevalence of the post-polio syndrome (PPS) is in estimated 50 % of persons with established poliomyelitis with a subsequently stable phase of at least 15 years. The basic mechanism is a loss of motoneuron cells in the spinal cord resulting in muscle weakness and fatigue. In addition pain, cold intolerance and a loss of stamina are frequently reported. There are few studies focusing on the orthopaedic symptoms in the PPS. This study should support the health-care professionals to the address the needs of PPS patients.A questionnaire was developed to collect data on patients who have been diagnosed by a neurologist as fulfilling the criteria of a PPS. It consists of two parts. In the first part, general patient data are collected. In the second part, details of health, pain, and activities of daily living are collected at two points in time: the time of the stable phase immediately after the acute phase of the disease and the phase after the PPS diagnosis. The questionnaires were sent to patients with a diagnosis of PPS. A total of 124 questionnaires were analysed (male: 45, female: 79). Parts of the data were used to calculate a score. It was hypothesised that the score would demonstrate a higher load of orthopaedic symptoms in the PPS phase.The results show that the phase after poliomyelitis (stable phase vs. PPS phase) was associated with significantly different sum score relating to the orthopaedic impairments. The score in the stable phase is on average 18.6 units lower than that in the post-PPS diagnosis phase (p < 0.001). The hypothesis that in the PPS phase the load of orthopaedic symptoms is increased is confirmed by our data. The "loss of functioning in the upper extremity" is also significantly associated with the score (p = 0.004).At the time the survey was taken, patients reveal a high level of musculoskeletal impairments and disabilities after PPS than during the stable phase with regard to general health as well as pain status and performance of daily activities. Age has no significant impact. Many of the patients are severely limited, especially with regard to activities such as walking, climbing stairs, and performing simple household tasks. Since there is no causal therapy for the underlying degeneration of the anterior horn cell pools, treatment is focused on the compensation of the functional limitations.
EVALuna2:5477

Pathway-Based Kernel Boosting for the Analysis of Genome-Wide Association Studies - Friedrichs, Stefanie; Manitz, Juliane; Burger, Patricia; Amos, Christopher I.; Risch, Angela; Chang-Claude, Jenny; Wichmann, Heinz-Erich; Kneib, Thomas; Bickeboeller, Heike; Hofner, Benjamin (Computational and Mathematical Methods in Medicine, 2017)
The analysis of genome-wide association studies (GWAS) benefits from the investigation of biologically meaningful gene sets, such as gene-interaction networks (pathways). We propose an extension to a successful kernel-based pathway analysis approach by integrating kernel functions into a powerful algorithmic framework for variable selection, to enable investigation of multiple pathways simultaneously. We employ genetic similarity kernels from the logistic kernel machine test (LKMT) as base-learners in a boosting algorithm. A model to explain case-control status is created iteratively by selecting pathways that improve its prediction ability. We evaluated our method in simulation studies adopting 50 pathways for different sample sizes and genetic effect strengths. Additionally, we included an exemplary application of kernel boosting to a rheumatoid arthritis and a lung cancer dataset. Simulations indicate that kernel boosting outperforms the LKMT in certain genetic scenarios. Applications to GWAS data on rheumatoid arthritis and lung cancer resulted in sparse models which were based on pathways interpretable in a clinical sense. Kernel boosting is highly flexible in terms of considered variables and overcomes the problem of multiple testing. Additionally, it enables the prediction of clinical outcomes. Thus, kernel boosting constitutes a new, powerful tool in the analysis of GWAS data and towards the understanding of biological processes involved in disease susceptibility.
EVALuna2:34213

Perioperative complications of scoliosis surgery in patients with Duchenne muscular dystrophy and spinal muscular atrophy, focussing on wound healing disorders - Burow, Mareike; Forst, Raimund; Forst, Jürgen; Hofner, Benjamin; Fujak, Albert (International Journal of Neuroscience, 2017)
Patients with Duchenne muscular dystrophy (DMD) or spinal muscular atrophy (SMA), both neuromuscular diseases, sustain spinal scoliosis in the course of their disease. To reduce the concomitant major morbidity and to improve their quality of life, patients require surgical spine stabilization. This can lead to complications like respiratory, cardiac or neurological complications or wound healing disorders (WHD). To find out the different complexities and risk factors increasing the chance to develop a WHD, the inpatient database was analyzed.We performed a retrospective statistical study. Therefore, we analyzed the inpatient database of 180 patients (142 DMD and 38 SMA patients). The focus was on WHD. To figure out the risk factors leading to WHD, we conducted a logistic regression.Cardiac complications occurred most frequently, followed by pulmonary complications and neurological lesions. Fifty-seven out of 180 patients developed a WHD. In 23 cases the WHD was aseptic, in the other 34 cases dermal organisms, Pseudomonas species and intestinal organisms were responsible. By means of the logistic regression, we were able to identify two more risk factors, in addition to diagnosis and gender, for developing a WHD in our patients: the year of surgery and the direction of pelvic tilt.Most common complications following scoliosis surgery are respiratory and cardiac complications. WHD is a severe complication that implies a prolonged therapy. Some risk factors for developing WHD could be identified in this analysis. Specifically, these were the date of surgery and the direction of pelvic tilt.
EVALuna2:10858

Plasma-Amino Acid-Levels and its Relation to Functionality and Muscle Mass in older Adults - Diekmann, R.; Hofner, Benjamin; Uter, Wolfgang; Kaiser, M.; Vidal, K.; Breuille, D.; Sieber, Cornel; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Predictive Modelling Based on Statistical Learning in Biomedicine - Gefeller, Olaf; Hofner, Benjamin; Mayr, Andreas; Waldmann, Elisabeth (Computational and Mathematical Methods in Medicine, 2017)
EVALuna2:34208

Predictive Value of Biomarker for Diagnosis and Prognosis of Acute Heart Failure in Geriatric Patients in the Emergency Room - Bahrmann, Philipp; Bertsch, T.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, A. (Zeitschrift für Gerontologie und Geriatrie, 2016)

Prognostic value of different biomarkers for cardiovascular death in unselected older patients in the emergency department - Bahrmann, Philipp; Christ, Michael; Hofner, Benjamin; Bahrmann, Anke; Achenbach, Susanne; Sieber, Cornel; Bertsch, Thomas (European Heart Journal: Acute Cardiovascular Care, 2016)
Risk stratification of elderly patients presenting with heart failure (HF) to an emergency department (ED) is an unmet challenge. We prospectively investigated the prognostic performance of different biomarkers in unselected older patients in the ED.We consecutively enrolled 302 non-surgical patients ?70 years presenting to the ED with a wide range of cardiovascular and non-cardiovascular comorbid conditions. N-terminal pro-B-type natriuretic peptide (NT-proBNP), mid-regional pro-adrenomedullin (MR-proADM), mid-regional pro-atrial natriuretic peptide (MR-proANP), C-terminal pro-endothelin-1 (CT-proET-1), ultrasensitive C-terminal pro-arginine-vasopressin (Copeptin-us) and high-sensitivity cardiac troponin T (hs-cTnT) were measured at admission. Two cardiologists independently adjudicated the final diagnosis of HF after reviewing all available baseline data using circulating NT-proBNP levels. A final diagnosis of HF was found in 120 (40%) of the 302 patients. All patients were followed up for cardiovascular death within the following 12 months. In order to test the prognostic performance of the investigated biomarkers we used boosting models with age and sex as mandatory covariates. Boosting is a statistical learning technique with built-in variable selection developed to obtain sparse and interpretable prediction models.Follow-up was 100% complete. During a median follow-up time of 225 days (interquartile range (IQR) 156-319 days), 30 (9.9%) of 302 patients (aged 81±6 years) had cardiovascular deaths. Of these 30 patients, 21 had HF and nine had no HF diagnosed prior to admission. The boosting model selected MR-proADM and hs-cTNT as predictors of cardiovascular deaths. The median values of MR-proADM and hs-cTnT at presentation were significantly higher in patients with cardiovascular deaths compared to surviving patients during follow-up (2.56 nmol/L (IQR 1.62-4.48) vs. 1.11 nmol/L (IQR 0.83-1.80), P<0.001 and 81 ng/L (IQR 38-340) vs. 17 ng/L (IQR 0.9-38), P=0.004). One unit increase in the log-transformed MR-proADM levels was associated with a 1.99-fold risk of death (95% confidence interval (CI) 1.61-2.45, P<0.001). The second marker, hs-cTnT, showed an increased predicted risk but was not significantly correlated to event-free survival (hazard ratio 3.22, 95% CI 0.97-10.68, P=0.056).Within different biomarkers, MR-proADM was the only predictor of cardiovascular deaths in unselected older patients presenting to the ED.
EVALuna2:10605

Quantification of Renal Function and Cardiovascular Mortality in Patients Admitted to the Emergency Department with Suspected Acute Coronary Syndromes - Bahrmann, Philipp; Bertsch, Thomas; Giannitsis, Evangelos; Christ, Michael; Hofner, Benjamin; Christenson, Robert; Lindahl, Bertil; Mueller, Christian (Clinical Laboratory, 2017)
BACKGROUND: Increases in the novel serum marker cystatin C are detectable much earlier in the course of chronic kidney disease (CKD) even when levels of serum creatinine are still in the normal range. A major factor causing a decrease in serum creatinine is increasing age. Patients with CKD are more likely to develop cardiovascular disease (CVD) than a healthy population and to suffer premature deaths from CVD related to CKD. The aim of this study was to investigate whether cystatin C, serum creatinine, and estimated glomerular filtration rate (eGFR) predict cardiovascular mortality in patients admitted to the emergency department (ED) with suspected acute coronary syndromes (ACS). METHODS: In 1,282 patients (mean age 62 ± 15 years, 477 women, 805 men) with suspected ACS, baseline cystatin C concentrations, serum creatinine, and estimated glomerular filtration rate (eGFR) were measured at the ED. Clinical assessment and serial high sensitivity cardiac troponin T (hs-cTnT) measurements were used for the diagnosis of ACS. Seventeen cardiovascular deaths were registered during a median follow-up of 365 days. RESULTS: HRs from univariate Cox regression models for each of the potential biomarkers were 12.02 (95% CI 5.10 - 28.34) for cystatin C, 4.53 (1.75 - 11.70) for serum creatinine, and 0.97 (0.96 - 0.99) for eGFR. All three biomarkers showed a significant association with cardiovascular mortality in univariate analyses. The HRs from a model with all three potential biomarkers were 59.21 (95% CI 9.69 - 361.76) for cystatin C, 0.08 (0.01 - 0.58) for serum creatinine, and 0.98 (0.96 - 1.01) for eGFR. The risk association was significant for ln (cystatin C) and ln (serum creatinine). CONCLUSIONS: Results of this prospective study show that the quantification of renal function using cystatin C is useful for predicting cardiovascular mortality in patients with suspected ACS at the ED.
EVALuna2:34209

Radiotherapy with paclitaxel/cisplatin vs. fluorouracil/cisplatin for head and neck cancer - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Iro, Heinrich; Gefeller, Olaf; Roedel, C.; Hautmann, M.; Koelbl, O.; Salay, A.; Ruebe, C.; Breinl, P.; Krings, W.; et al. (RADIOTHERAPY AND ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-06-18

Randomized phase-III-trial of concurrent chemoradiation for locally advanced head and neck cancer comparing dose reduced radiotherapy with paclitaxel/cisplatin to standard radiotherapy with fluorouracil/cisplatin: The PacCis-trial - Fietkau, Rainer; Hecht, Markus; Hofner, Benjamin; Lubgan, Dorota; Iro, Heinrich; Gefeller, Olaf; Rödel, Claus; Hautmann, Matthias G.; Kölbl, Oliver; Salay, Attila; Rübe, Christian; Melchior, Patrick; et al. (Radiotherapy and Oncology, 2020)
Background and purpose: This multicenter, phase 3 trial investigates whether the incorporation of concurrent paclitaxel and cisplatin together with a reduced total dose of radiotherapy is superior to standard fluorouracil–cisplatin based CRT. Materials and methods: Patients with SCCHN, stage III–IVB, were randomized to receive paclitaxel/cisplatin (PacCis)–CRT (arm A; paclitaxel 20 mg/m2 on days 2, 5, 8, 11 and 25, 30, 33, 36; cisplatin 20 mg/m2, days 1–4 and 29–32; RT to a total dose of 63.6 Gy) or fluorouracil/cisplatin (CisFU)–CRT (arm B; fluorouracil 600 mg/m2; cisplatin 20 mg/m2, days 1–5 and 29–33; RT: 70.6 Gy). Endpoint was 3-year-disease free survival (3y-DFS). Results: A total of 221 patients were enrolled between 2010 and 2015. With a median follow-up of 3.7 years, 3y-DFS in the CisFU arm and PacCis arm was 58.2% and 48.4%, respectively (HR 0.82, 95% CI 0.56–1.21, p = 0.52). The 3y-OS amounted to 64.6% in the CisFU arm, and to 59.2% in the PacCis arm (HR 0.82, 95% CI 0.54–1.24, p = 0.43). In the subgroup of p16-positive oropharyngeal carcinomas, 3y-DFS and 3y-OS was 84.6% vs 83.9% (p = 0.653), and 92.3% vs. 83.5% (p = 0.76) in arm A and B, respectively. Grade 3–4 hematological toxicities were significantly reduced in arm A (anemia, p = 0.01; leukocytopenia, p = 0.003), whereas grade 3 infections were reduced in arm B (p = 0.01). Conclusion: Paclitaxel/cisplatin–CRT with a reduced RT-dose is not superior to standard fluorouracil/cisplatin–CRT. Subgroup analyses indicate that a reduced radiation dose seems to be sufficient for p16+ oropharyngeal cancer or non-smokers. Clinical trial information: NCT01126216; EudraCT Number 2005-003484-23.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Chemoradiotherapy; Cisplatin; Fluorouracil; Head and neck cancer; Paclitaxel

Regulatory Issues of Platform Trials: Learnings from EU-PEARL - Nguyen, Quynh Lan; Hees, Katharina; Hernandez Penna, Sabina; König, Franz; Posch, Martin; Bofill Roig, Marta; Meyer, Elias Laurin; Freitag, Michaela Maria; Parke, Tom; Otte, Maximilian; Dauben, Hans Peter; Mielke, Tobias; et al. (Clinical Pharmacology & Therapeutics, 2024)
Although platform trials have many benefits, the complexity of these designs may result not only in increased methodological but also regulatory and ethical challenges. These aspects were addressed as part of the IMI project EU Patient-Centric Clinical Trial Platforms (EU-PEARL). We reviewed the available guidelines on platform trials in the European Union and the United States. This is supported and complemented by feedback received from regulatory interactions with the European Medicines Agency and the US Food and Drug Administration. Throughout the project we collected the needs of all relevant stakeholders including ethics committees, regulators, and health technology assessment bodies through active dialog and dedicated stakeholder workshops. Furthermore, we focused on methodological aspects and where applicable identified the corresponding guidance. Learnings from the guideline review, regulatory interactions, and workshops are provided. Based on these, a master protocol template was developed. Issues that still need harmonization or clarification in guidelines or where further methodological research is needed are also presented. These include questions around clinical trial submissions in Europe, the need for multiplicity control across the whole master protocol, the use of non-concurrent controls, and the impact of different randomization schemes. Master protocols are an efficient and patient-centered clinical trial design that can expedite drug development. However, they can also introduce additional operational and regulatory complexities. It is important to understand the different requirements of stakeholders upfront and address them in the trial. While relevant guidance is increasing, early dialog with relevant stakeholders can help to further support such designs.
CRIS-Team Scopus Importer:2024-04-12

Reproducible research in statistics: A review and guidelines for the Biometrical Journal - Hofner, Benjamin; Schmid, Matthias; Edler, Lutz (Biometrical Journal, 2016)
Reproducible research (RR) constitutes the idea that a publication should be accompanied by all relevant material to reproduce the results and findings of a scientific work. Hence, results can be verified and researchers are able to build upon these. Efforts of the Biometrical Journal over the last five years have increased the number of manuscripts which are reproducible by a factor of 4 to almost 50%. Yet, more than half of the code submission could not be executed in the initial review due to missing code, missing data or errors in the code. Careful checks of the submitted code as part of the reviewing process are essential to eliminate these issues and to foster RR. In this article, we reviewed n=56 recent submissions of code and data to identify common reproducibility issues. Based on these findings, guidelines for structuring code submission to the Biometrical Journal have been established to help authors. These guidelines should help researchers to implement RR in general. Together with the code reviews, this supports the mission of the Biometrical Journal in publishing highest quality, novel and relevant papers on statistical methods and their applications in life sciences. Source code and data to reproduce the presented data analyses are available as Supplementary Material on the journal's web page.
EVALuna2:5555

Stochastic Dispersal Rather Than Deterministic Selection Explains the Spatio-Temporal Distribution of Soil Bacteria in a Temperate Grassland - Richter-Heitmann, Tim; Hofner, Benjamin; Krah, Franz Sebastian; Sikorski, Johannes; Wüst, Pia K.; Bunk, Boyke; Huang, Sixing; Regan, Kathleen M.; Berner, Doreen; Boeddinghaus, Runa S.; Marhan, Sven; Prati, Daniel; et al. (Frontiers in Microbiology, 2020)
Spatial and temporal processes shaping microbial communities are inseparably linked but rarely studied together. By Illumina 16S rRNA sequencing, we monitored soil bacteria in 360 stations on a 100 square meter plot distributed across six intra-annual samplings in a rarely managed, temperate grassland. Using a multi-tiered approach, we tested the extent to which stochastic or deterministic processes influenced the composition of local communities. A combination of phylogenetic turnover analysis and null modeling demonstrated that either homogenization by unlimited stochastic dispersal or scenarios, in which neither stochastic processes nor deterministic forces dominated, explained local assembly processes. Thus, the majority of all sampled communities (82%) was rather homogeneous with no significant changes in abundance-weighted composition. However, we detected strong and uniform taxonomic shifts within just nine samples in early summer. Thus, community snapshots sampled from single points in time or space do not necessarily reflect a representative community state. The potential for change despite the overall homogeneity was further demonstrated when the focus shifted to the rare biosphere. Rare OTU turnover, rather than nestedness, characterized abundance-independent β-diversity. Accordingly, boosted generalized additive models encompassing spatial, temporal and environmental variables revealed strong and highly diverse effects of space on OTU abundance, even within the same genus. This pure spatial effect increased with decreasing OTU abundance and frequency, whereas soil moisture – the most important environmental variable – had an opposite effect by impacting abundant OTUs more than the rare ones. These results indicate that – despite considerable oscillation in space and time – the abundant and resident OTUs provide a community backbone that supports much higher β-diversity of a dynamic rare biosphere. Our findings reveal complex interactions among space, time, and environmental filters within bacterial communities in a long-established temperate grassland.
CRIS-Team Scopus Importer:2020-07-31
Keywords: community assembly; generalized additive model; soil bacteria communities; spatio-temporal analysis; variable selection

Success of a deadwood enrichment strategy in production forests depends on stand type and management intensity - Doerfler, Inken; Mueller, Joerg; Gossner, Martin M.; Hofner, Benjamin; Weisser, Wolfgang W. (Forest Ecology and Management, 2017)
The increasing demand for wood products increases the anthropogenic pressure on biodiversity in forests. Thereby integrative nature conservation strategies, allowing for both, wood production and biodiversity conservation, increase in importance. While many of such strategies are now implemented, the success is often unclear. We evaluated the success of a deadwood enrichment strategy in a large hardwood production forest shortly (four and nine years) after its implementation. We compared plot wise data of deadwood amounts in managed stands of an even aged high forest and forest nature reserves before and after the implementation of the strategy, and used generalized additive boosting models to identify major drivers of deadwood amounts and deadwood enrichment. Deadwood amounts before and after the implementation of the strategy were affected by stand age, natural tree mortality and tree species composition. The highest amounts of deadwood were found in stands around 100 years old, with a high natural mortality and a high percentage of deciduous trees. Harvesting intensity was a strong driver of deadwood enrichment. Besides that we found smaller differences between managed and unmanaged forests after the implementation. We conclude that active deadwood enrichment can be a valuable tool to increase deadwood amounts in production forests. (c) 2017 Elsevier B.V. All rights reserved.
EVALuna2:34178

The betaboost package-a software tool for modelling bounded outcome variables in potentially high-dimensional epidemiological data - Mayr, Andreas; Weinhold, Leonie; Hofner, Benjamin; Titze, Stephanie; Gefeller, Olaf; Schmid, Matthias (International Journal of Epidemiology, 2018)
Motivation: To provide an integrated software environment for model fitting and variable selection in regression models with a bounded outcome variable. Implementation: The proposed modelling framework is implemented in the add-on package betaboost of the statistical software environment R. General features: The betaboost methodology is based on beta-regression, which is a state-of-the-art method for modelling bounded outcome variables. By combining traditional model fitting techniques with recent advances in statistical learning and distributional regression, betaboost allows users to carry out data-driven variable and/or confounder selection in potentially high-dimensional epidemiological data. The software package implements a flexible routine to incorporate linear and non-linear predictor effects in both the mean and the precision parameter (relating inversely to the variance) of a beta-regression model. Availability: The software is hosted publicly at [http://github.com/boost-R/betaboost] and has been published under General Public License (GPL) version 3 or newer.
EVALuna2:35660

Vaccine Development during a Pandemic: General Lessons for Clinical Trial Design - Hofner, Benjamin; Asikanius, Elina; Jacquet, Wolfgang; Framke, Theodor; Oude Rengerink, Katrien; Aguirre Dávila, Lukas; Grünewald, Maria; Klinglmüller, Florian; Posch, Martin; Leacy, Finbarr P.; Lang, Thomas; Koch, Armin; et al. (Statistics in Biopharmaceutical Research, 2023)
The COVID-19 pandemic triggered an unprecedented research effort to develop vaccines and therapeutics. Urgency dictated that development and regulatory assessment were accelerated, while maintaining all standards for quality, safety and efficacy. To speed up evaluation the European Medicines Agency (EMA) implemented “rolling reviews” allowing developers to submit data for assessment as they became available. We discuss the clinical trial designs and the applied statistical approaches in vaccine efficacy trials, focusing on aspects such as multiple testing, interim and updated analyses, and reporting of results for the first four vaccines recommended for approval by the EMA. The fast accrual of COVID-19 cases in the clinical vaccine efficacy trials led to multiple data updates within a short time frame, which had consequences for the evaluation and interpretation of results. Key trial results are discussed in the light of these aspects. Notably, the aspects discussed did not affect the benefit/risk relationship in a meaningful way, which was clearly positive for all four vaccines. Assessment of the development and evaluation of the four vaccine trials during the pandemic has led to a proposal for standardized terminology for trials with multiple analyses and a recommendation to appropriately preplan the timing of primary and updated analyses. For the reporting of updated estimates of vaccine efficacy, we discuss how to best describe the uncertainty around estimates of vaccine efficacy (e.g., via confidence intervals). Finally, we briefly highlight the benefit of a comprehensive discussion on estimands for vaccine efficacy trials. Supplementary materials for this article are available online.
CRIS-Team Scopus Importer:2023-09-29
Keywords: COVID-19; Interim analyses; Reporting of results; Updated analyses; Vaccine efficacy